2016
DOI: 10.1530/erc-16-0084
|View full text |Cite
|
Sign up to set email alerts
|

Hormone receptor status does not alter the effect of trastuzumab in breast cancer

Abstract: Overexpression of human epidermal growth factor receptor 2 (HER2) predicts response to anti-HER2 therapy in breast cancer. We investigated whether hormone receptor (HR) status influences the treatment benefit of trastuzumab in patients with breast cancer. Data from 8338 patients with primary nonmetastatic breast cancer from the cancer registry of Saxony-Anhalt Germany were analyzed. A total of 5554 patients were eligible for analysis. The median follow-up of the study was 6 years. Of the 5554 patients investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…In contrast, Brufsky et al (2005) and Dawood et al (2010) demonstrated that HR-positive disease was associated with improved clinical outcomes in patients with metastatic BC. Recently, a large cohort study in German also showed that anti-HER2 agents improved patients' survival regardless of HR status (Ignatov et al 2016). It is noted that all these trials were retrospective studies and the primary aims of each trials were different, so these result should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Brufsky et al (2005) and Dawood et al (2010) demonstrated that HR-positive disease was associated with improved clinical outcomes in patients with metastatic BC. Recently, a large cohort study in German also showed that anti-HER2 agents improved patients' survival regardless of HR status (Ignatov et al 2016). It is noted that all these trials were retrospective studies and the primary aims of each trials were different, so these result should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%